Dissociative Bioorthogonal Reactions. (25th April 2019) - Tu, Julian; Xu, Minghao; Franzini, Raphael M.
Abstract: Bioorthogonal reactions that proceed readily under physiological conditions without interference from biomolecules have found widespread application in the life sciences. Complementary to the bioorthogonal reactions that ligate two molecules, reactions that release a molecule or cleave a linker are increasingly attracting interest. Such dissociative bioorthogonal reactions have a broad spectrum of uses, for example, in controlling bio‐macromolecule activity, in drug delivery, and in diagnostic assays. This review article summarizes the developed bioorthogonal reactions linked to a release step, outlines representative areas of the applications of such reactions, and discusses aspects that require further improvement. Abstract : Breaking up is not so hard : Parallel to reactions that ligate two entities, reactions that instead release molecules or cleave linkers under physiological conditions without interference from biological components are increasingly being developed. We here summarize examples of such dissociative bioorthogonal reactions and outline their application in the chemical biology and biomedical sciences.